Two decades of subcutaneous glatiramer acetate injection: current role of the standard dose, and new high-dose low-frequency glatiramer acetate in relapsing–remitting multiple sclerosis treatment - Caporro, Matteo (Dove Medical Press, 2014)
Glatiramer acetate, a synthetic amino acid polymer analog of myelin basic protein, is one of the first approved drugs for the treatment of relapsing–remitting multiple sclerosis. Several clinical trials have shown consistent and sustained efficacy of glatiramer acetate 20 mg subcutaneously daily in reducing relapses and new demyelinating lesions on magnetic resonance imaging in patients with relapsing–remitting multiple sclerosis, as well as comparable efficacy to high-dose interferon beta. Some preclinical and clinical data suggest a neuroprotective role for glatiramer acetate in multiple sclerosis. Glatiramer acetate is associated with a relatively favorable side-effect profile, and importantly this was confirmed also during long-term use. Glatiramer acetate is the only multiple sclerosis treatment compound that has gained the US Food and Drug Administration pregnancy category B. All these data support its current use as a first-line treatment option for patients with clinical isolated syndrome or relapsing–remitting multiple sclerosis. More recent data have shown that high-dose glatiramer acetate (ie, 40 mg) given three times weekly is effective, safe, and well tolerated in the treatment of relapsing–remitting multiple sclerosis, prompting the approval of this dosage in the US in early 2014. This high-dose, lower-frequency glatiramer acetate might represent a new, more convenient regimen of administration, and this might enhance patients’ adherence to the treatment, crucial for optimal disease control.